Similarities Between Somatosensory Cortical Responses Induced via Natural Touch and Microstimulation in the Ventral Posterior Lateral Thalamus in Macaques - Francis, Joseph Thachil; Rozenboym, Anna; von Kraus, Lee; Xu, Shaohua; Chhatbar, Pratik; Semework, Mulugeta; Hawley, Emerson; Chapin, John (Frontiers in Neuroscience, 2022)
Lost sensations, such as touch, could be restored by microstimulation (MiSt) along the sensory neural substrate. Such neuroprosthetic sensory information could be used as feedback from an invasive brain-machine interface (BMI) to control a robotic arm/hand, such that tactile and proprioceptive feedback from the sensorized robotic arm/hand is directly given to the BMI user. Microstimulation in the human somatosensory thalamus (Vc) has been shown to produce somatosensory perceptions. However, until recently, systematic methods for using thalamic stimulation to evoke naturalistic touch perceptions were lacking. We have recently presented rigorous methods for determining a mapping between ventral posterior lateral thalamus (VPL) MiSt, and neural responses in the somatosensory cortex (S1), in a rodent model (Choi et al., 2016; Choi and Francis, 2018). In our technique, we minimize the difference between S1 neural responses induced by natural sensory stimuli and those induced via VPL MiSt. The goal is to develop systems such that we know what MiSt to use to produce a given neural response and possibly a more natural "sensation”. To date, our optimization has been conducted in the rodent model and simulations. Here we present data from simple non-optimized thalamic MiSt during peri-operative experiments, where we MiSt in the VPL of macaques with a somatosensory system more like humans. We implanted arrays of microelectrodes across the hand area of the macaque S1 cortex as well as in the VPL thalamus. Multi and single-unit recordings were used to compare cortical responses to natural touch and thalamic MiSt in the anesthetized state. Post stimulus time histograms could be highly correlated between the VPL MiSt and natural touch modalities, indicating VPL MiSt may be suitable for producing a somatosensory neuroprosthesis in humans.